Artificial Intelligence in Breach Detection : Need of the Hour for Password Management - Bansal, Nitin (Indian Journal of Finance, 2026)
Purpose : The purpose of this study was to examine the role of artificial intelligence (AI) in strengthening the breach detection mechanisms and addressing emerging challenges in password management (PM). Design/Methodology/Approach : The study adopted a quantitative research design and used primary data from 413 respondents from the National Capital Region, India. The partial least squares-structural equation modeling (Smart PLS-SEM) version 4.1.1.2 method was used to examine the moderating effect of AI on PM. Findings : The study found that AI impacted password generation, automated threat detection, password reuse detection, user experience, password cracking detection, and password recovery, which led to PM. Practical Implications : The study highlighted the need for organizations to integrate AI-enabled security solutions to proactively mitigate password-related cyber threats and data breaches. Originality/Value : This paper contributed to the cybersecurity literature by emphasizing AI as a timely and essential solution for modern breach detection and effective PM in an evolving digital environment.